The rooster crows : a book of American rhymes and jingles - Petersham, Maud, 1890-1971.; Petersham, Miska, 1888-1960. (New York : Aladdin Books ; London : Collier Macmillan, 1987)
A collection of traditional American nursery rhymes, finger games, skipping rhymes, jingles, and counting-out rhymes.
Keywords: Nursery rhymes, American; Children's poetry, American; Nursery rhymes; American poetry; Caldecott Medal